Examining classroom transformational spaces using the third space theory in developing students’ sense of shared identity - Idrus, Faizah (Academy Publication, 2015)
This article reports the investigation that seeks to address the possibility of using selected texts in the English language classrooms that could develop students’ sense of shared identity. In so doing, this study attempts to examine perceptions of teachers and students about classroom collaborations between studentsstudent and student-teacher using case-based narratives which was selected by teachers. It also seeks to identify how their collaborative acts can be suggestive to transforming a linear classroom lesson to a more vibrant and effective one and simultaneously develop students sense of shared identity. A qualitative inquiry employing semi-structured interviews, classroom observations and group interviews with 12 secondary English language school teachers and their students were conducted. Teachers’ classroom practices (and instructions) are then analysed to gauge their impact on students’ interactions with each other during task completion. The preliminary results indicate that teachers’ were reluctant to relinquish their authority and power to students for various reasons which could be detrimental to the construction of shared identity. Teachers, more than students felt that their authoritative figure were one of the key indicators of classroom progress in a result-driven education system. The results obtained aim to be informative in pointing to the viability of providing avenues for syllabus designers or other stakeholders to take into considerations texts types which could be used for secondary schools English Literature syllabus in developing students sense of shared identity. Meanwhile, it is also found that students’ sense of shared identity could be halted without teachers’ support and encouragement of these transformational learning spaces.